THE IMPACT OF COVID-19 ON THE LIFESTYLE OF BRAZILAN INDIGENOUS PEOPLES IN LIGHT OF THE 2030 AGENDA - Bonetti, Camila; Bottoni, Irineu Jose; Rocha, Renan Conte; de Benedicto, Samuel Carvalho; Longo, Regina Marcia; Mariosa, Duarcides Ferreira; da Silva, Marcelo Pereira; Ferrari, Vinícius Eduardo (ARACÊ, 2025)
In Brazil, during the COVID-19 pandemic, the sustainability of society has been put to the test and human fragility has been exposed, especially that of indigenous peoples. This study analyzes the impact of COVID-19 on the indigenous peoples of Brazil, in light of the five critical elements of the 2030 Agenda: people, prosperity, planet, partnership and peace. This is an applied study with a qualitative, descriptive and explanatory approach. The data was collected through bibliography, using official documents and publications and academic literature, with emphasis on the award-winning indigenous author Ailton Krenak. The results show that the COVID-19 pandemic can be understood as a warning about the vulnerability of the human species, with special emphasis on indigenous peoples.  The conclusion is that a substantial and applicable knowledge of the critical dimensions of the 2030 Agenda involves environmental education, which must be inserted into the daily lives of society and the constituted authorities.